Characterization of intense ion beam energy density and beam induced pressure on the target with acoustic diagnostics - Pushkarev A. I. Aleksandr Ivanovich; Isakova Yu. I. Yulia Ivanovna; Xiao Y.; Khailov (Khaylov) I. P. Iliya Pavlovich (2013, 2013)
Title screen